INFRASTRUCTURE AND SECURITY DILEMMA: ANALYSING MISTRUST AND CONFLICTS IN INDIA-CHINA BORDER RELATIONS (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Territorial disputes between India and China along the Line of Actual Control (LAC) have increasingly been marked by China’s extensive infrastructure development in contested areas. Based on its longstanding practices, notably the construction of the Great Wall of China, a boundary that also served as a symbolic marker of control and strategic domination, China’s contemporary infrastructure initiatives in Tibet and Aksai Chin are reflective of a landscape of build to consolidate. Such dual-use development/militarization projects further compound India’s security dilemma and have therefore necessitated developing defensive countermeasures like the Darbuk-Shyok-Daulat Beg Oldie Road and airstrip. Booth and Wheeler (Booth and Wheeler 2008)’s Security Dilemma is used in this study to explore how China’s offensive infrastructure expansion compels India’s reactionary infrastructural arms raceresulting in an intensifying cycle of this mistrust and escalation of conflict. The Galwan Clash of 2020 is one of several events that have shown how Chinese aggressive moves have changed the strategic-spatial context of the region along the LAC. This asymmetric infrastructure competition places India in a reactive posture and makes it must weigh territorial security against strategic restraint.This paper underscores that the infrastructure plays a significant role in exacerbating security dilemma between India China border relations.